Diskriminasi Gender sebagai Dampak Patriarkal Oppresi dalam Novel Seven Husband of Evelyn oleh Taylor Jenkins - Rosmiati (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This thesis aims to analyze the forms of gender discrimination and how patriarchy can affect gender discrimination. This study aims to explain feminism, patriarchy, and gender discrimination experienced by female characters in the novel which is the object of this research. This study uses feminism theory with a radical feminism approach proposed by Alison Jaggar and uses patriarchy from Sylvia Walby as a supporting theory. In this study, feminism theory is used to explain and analyze gender discrimination forms. The method used in this research is the descriptive qualitative method. In this study, researchers found gender discrimination forms accepted by female figures and patriarchal oppression forms that could affect gender discrimination.